Regeneration of immature incisor using platelet rich fibrin: report of a novel clinical application - Jishnu Krishna Kumar; Padmapriya Surendranath; Rajalakshmanan Eswaramoorthy (BMC, 2023)
Abstract Background Endodontic treatment of young permanent teeth with necrotic pulp presents a clinical challenge for the dentist, and conventional endodontic treatment will result in tooth fracture along with a poor prognosis. Regenerative endodontics is a new protocol that has been advanced in the last decades for managing immature permanent teeth. Rare successful management of immature permanent incisors using platelet-rich fibrin is a technique-sensitive procedure. Case presentation A 08 years 04 months old female reported the chief complaint of pain in the upper front tooth region for one week. A blunderbuss canal was identified on radiographic examination, and revascularization using platelet-rich fibrin was planned and adopted. After the treatment, apical closure and root lengthening were noted without complications during subsequent follow-ups. Complete periapical healing with greater than 1.5 cm of dentinal thickness was noted. Conclusion Revascularization can be considered a viable treatment option for immature nonvital permanent teeth; with advancements in regenerative medicine and clinical practices, revascularization therapies could be developed as a novel mode of treatment in non-vital and dental traumatic cases.